Evaluation of A-site cation-deficient (Ba0.5Sr0.5)1-xCo0.8Fe0.2O3-d (x > 0) perovskite as a solid-oxide fuel cell cathode - Zhou, W.; Ran, R.; Shao, Zongping; Jin, W.; Xu, N. (Elsevier SA, 2008)
A-site cation-deficient (Ba0.5Sr0.5)1-xCo0.8Fe0.2O3-d ((BS)1-xCF) oxides were synthesized and evaluated as cathode materials for intermediate-temperature solid-oxide fuel cells (ITSOFCs). The material's thermal expansion coefficient, electrical conductivity, oxygen desorption property, and electrocatalytic activity were measured. A decrease in both the electronic conductivity and the thermal expansion coefficient was observed for increasing values of the stoichiometric coefficient, x. This effect was attributed to the creation of additional oxygen vacancies, the suppression of variation in the oxidation states of cobalt and iron, and the suppression of the spin-state transitions of cobalt ions. The increase in A-site cation deficiency resulted in a steady increase in cathode polarization resistance, because impurities formed at the cathode/electrolyte interface, reducing the electronic conductivity. A single SOFC equipped with a BS0.97CF cathode exhibited peak power densities of 694 and 893 mW cm-2 at 600 and 650 °C, respectively, and these results were comparable with those obtained with a Ba0.5Sr0.5Co0.8Fe0.2O3-d cathode. Slightly A-site cation-deficient (BS)1-xCF oxides were still highly promising cathodes for reduced temperature SOFCs. © 2008 Elsevier B.V. All rights reserved.